2011
DOI: 10.1002/chem.201002685
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrotropylium–Co2(CO)6 Ion: Generation, Reactivity and Evaluation of Cation Stability

Abstract: Dehydrotropylium-Co 2 (CO) 6 ion, 1, has been generated by the action of HBF 4 or BF 3 ·OEt 2 on the corresponding cycloheptadienynol complex 7, which in turn has been prepared in four steps from a known diacetoxycycloheptenyne complex. The reaction of 7 via 1 with several nucleophiles results in substitution reactions with reactive nucleophiles (N > 1) under normal conditions, and a radical dimerization reaction in the presence of less reactive nucleophiles. Competitive reactions of 7 with an acyclic trienyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…In contrast, the previously studied antiaromatic fluorenyl, indenyl and cyclopentadienyl cluster-stabilised cations, 10, 11 and 12, might be considered as developing pentafulvenec haracter thus losing their antiaromatic character.I nterestingly,i nt he course of his elegant studies of the synthetic utility of cycloheptyne-dicobalt clusters, [48] Green showedt hat the [Co 2 (CO) 6 (dehydrotropylium)] + cation is only weakly aromatic. [49] Furthermore, we note that the effecto fat ricarbonylchromium fragment on the thermodynamic stability of benzylc ations was investigated many years ago by Ceccon et al [50] It was shown from pK R + measurements that incorporation of the [Cr(CO) 3 ]g roup can render the complexed cation more, or less, stable than the correspondingf ree ion, and is dependent on both electronic and conformational effects. Finally,s ome qualitative electronic considerations may help to frame the nature of the bondingi nm ore familiar terms.…”
Section: Computational Approachmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, the previously studied antiaromatic fluorenyl, indenyl and cyclopentadienyl cluster-stabilised cations, 10, 11 and 12, might be considered as developing pentafulvenec haracter thus losing their antiaromatic character.I nterestingly,i nt he course of his elegant studies of the synthetic utility of cycloheptyne-dicobalt clusters, [48] Green showedt hat the [Co 2 (CO) 6 (dehydrotropylium)] + cation is only weakly aromatic. [49] Furthermore, we note that the effecto fat ricarbonylchromium fragment on the thermodynamic stability of benzylc ations was investigated many years ago by Ceccon et al [50] It was shown from pK R + measurements that incorporation of the [Cr(CO) 3 ]g roup can render the complexed cation more, or less, stable than the correspondingf ree ion, and is dependent on both electronic and conformational effects. Finally,s ome qualitative electronic considerations may help to frame the nature of the bondingi nm ore familiar terms.…”
Section: Computational Approachmentioning
confidence: 84%
“…In contrast, the previously studied antiaromatic fluorenyl, indenyl and cyclopentadienyl cluster‐stabilised cations, 10 , 11 and 12 , might be considered as developing pentafulvene character thus losing their antiaromatic character. Interestingly, in the course of his elegant studies of the synthetic utility of cycloheptyne–dicobalt clusters, Green showed that the [Co 2 (CO) 6 (dehydrotropylium)] + cation is only weakly aromatic . Furthermore, we note that the effect of a tricarbonylchromium fragment on the thermodynamic stability of benzyl cations was investigated many years ago by Ceccon et al .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of reactions with thiophene and mesitylene, a larger excess of nucleophile was employed (10 equiv), given the propensity we have seen previously for polysubstitution in Nicholas reactions on relatively weak nucleophiles. 20 Thiophene (N = -1.01) gave 11d solely (80%, 11d/11d′ > 98:2, Table 1, entry 6), but with some C-3 substitution of the thiophene (C-2/C-3 = 88:12); mesitylene gave 11e in 73% yield (11e/11e′ > 98:2, Table 1, entry 8). Lowering the reaction temperature to -78 °C still allowed prompt reaction and improved the results in some cases.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…178 The substitution of a leaving group, such as propargylic acetate, with heteroatom-and carbon-based nucleophiles is highly chemoselective in that it avoids the formation of allenes. Recent investigations of heteroatom nucleophiles involve the formation of bispropargylic ethers, 179 cyclic polyethers, 180,181 propargylic azides, 182 dithia-and thia-oxacyclooctynes, 183 seven-and eight-membered cyclic ethers 184 and carbacycles [185][186][187] with a cobalt-protected triple bond as well as the formation of 5-alkynylproline derivatives. 188 The dicobalt hexacarbonyl moiety is able to stabilise cationic species which can be attacked by nucleophiles.…”
Section: Nicholas Reactionsmentioning
confidence: 99%